The Lasallian InSPIRE: International students program for involvement in responsive exchange: (A program for DLSU exchange and international students) - Abaya, Adel (Animo Repository, 2017)
Internationalization in higher education is now a world-wide phenomenon. The increase in the number of international students drives universities to look at their programs and services to ensure that they are able to assist their international students towards effective adjustment to their host country and host university. While other universities around the world continue to develop more programs and expand existing programs to attract more international students, other universities are focusing their internationalization efforts on existing programs and services and how these could be improved to make them more responsive to the need of these special students. Similarly, De La Salle University, while moving towards strengthening its internationalization efforts in the areas of students and student programs, would like to ensure that its international student population is able to enjoy a campus environment that supports multiculturalism and diversity. As a response, this program of development materials supports this goal by providing the exchange and international students of DLSU with necessary support in terms of their organizational and adjustment needs during the duration of their student exchange program. Results of data from needs assessment and exit survey administered to exchange students were utilized as bases for program development. The program, called Lasallian InSPIRE, or the international students program for involvement in responsive exchange, consists of core and supplemental activities that are primarily designed to address the adjustment needs of the international students. The program gives them opportunities for social interaction, development of psychosocial skills for effective adjustment, and enhancement of their intercultural effectiveness. It is an integrated learning and development program which runs for one trimester and allows participants to take full advantage of their student exchange experience at DLSU. The participants are short-term inbound exchange students, self-paying and cross-enrollees for partner and non-partner universities abroad, special/audit students, and few regular students. The activities of InSPIRE provide participants with opportunities to interact with the local students, experience Filipino culture, play Filipino traditional games, join cultural exposure trips, social gatherings, and psychosocial activities and skills enhancement seminars among others. An immediate evaluation checklist is administered to participants at the end of each activity. Through the effective, consistent, and efficient implementation of InSPIRE, exchange and international students are expected to bring back with them the meaningful learning experiences that they have gained during the duration of their student exchange program. For the purpose of program improvement, it is recommended that an evaluation study of the effectiveness of InSPIRE is conducted through a thorough review and analysis of its program evaluation schemes.